A Community-Based Cluster Randomized Controlled Trial of "Directly Observed Home-Based Daily Iron Therapy" in Lowering Prevalence of Anemia in Rural Women and Adolescent Girls. (March 2015) - Bharti, Sahul; Bharti, Bhavneet; Naseem, Shano; Attri, Savita Verma
In a community-based cluster randomized controlled trial, we randomly assigned clusters of anemic women and adolescent girls to either "directly observed home-based daily iron therapy" (DOHBIT; n = 524 in 16 villages) or unsupervised self-treatment at home (n = 535 in 16 villages) for a period of 90 days. Those in the DOHBIT group, when compared with those in the unsupervised self-treatment group, had significantly lower relative risk (RR) of anemia (16.8% vs 35.3%, RR = 0.47 [95% confidence interval (CI) = 0.33-0.65]; P < .0001), higher hemoglobin (Hb) rise of ≥2 g/dL (70.2% vs 42.2%, RR = 1.56 [95% CI = 1.31-1.87]; P <.0001), and nonsignificant trend for lower side effects (3.5% vs 6.7%, RR = 0.49 [95% CI = 0.22-1.08; P < .08) on intention-to-treat analyses. On linear mixed model analysis, the subjects in the intervention group demonstrated higher mean Hb levels (13.01 vs 12.32 g/dL; P < .0001) and higher adherence to iron therapy (93% vs 60%; P < .0001). DOHBIT is effective in lowering the prevalence of anemia in rural women and adolescent girls.